Iron deficiency among blood donors: experience from the Danish Blood Donor Study and from the Copenhagen ferritin monitoring scheme. (10th October 2017) - Rigas, A. S.; Pedersen, O. B.; Magnussen, K.; Erikstrup, C.; Ullum, H.
SUMMARY: Blood components collected from blood donors are an invaluable part of modern‐day medicine. A healthy blood donor population is therefore of paramount importance. The results from the Danish Blood Donor Study (DBDS) indicate that gender, number of previous donations, time since last donation and menopausal status are the strongest predictors of iron deficiency. Only little information on the health effects of iron deficiency in blood donors exits. Possibly, after a standard full blood donation, a temporarily reduced physical performance for women is observed. However, iron deficiency among blood donors is not reflected in a reduced self‐perceived mental and physical health. In general, the high proportion of iron‐deficient donors can be alleviated either by extending the inter‐donation intervals or by guided iron supplementation. The experience from Copenhagen, the Capital Region of Denmark, is that routine ferritin measurements and iron supplementation are feasible and effective ways of reducing the proportion of donors with low haemoglobin levels.